The concept of "domino" in liver and hepatocyte transplantation. (October 2020) - Zhou, Guang-Peng; Sun, Li-Ying; Zhu, Zhi-Jun
Although orthotopic liver transplantation remains the only proven treatment for end-stage liver disease and inherited metabolic liver disease, its application has been limited by the scarcity of donor organs available for transplantation. Among feasible approaches developed to expand the donor organ pool, domino liver transplantation is a strategy in which explanted genetically defective livers of liver transplant recipients are used as grafts in other patients. Another promising therapeutic strategy is hepatocyte transplantation, an alternative to liver transplantation for certain groups of patients. However, the availability of primary hepatocytes is also hindered by the shortage of donor liver tissues. Against this background, domino hepatocyte transplantation, a strategy that utilizes the hepatocytes derived from the explanted livers of liver transplant recipients with noncirrhotic inherited metabolic liver diseases as the source of primary hepatocytes, may help increase the supply of liver cells available for transplantation. In this review, we focus on the status quo of domino liver transplantation and domino hepatocyte transplantation. We also describe recent innovative transplant strategies based on domino transplantation.